Enhancement of the catalytic activity of Mg/Al layered double hydroxide for glycerol oligomers production - Soares Barros, Fernando José; Liu, Yue; Dantas Paula, Clarissa; Murilo Tavares de Luna, Francisco; Silveira Vieira, Rodrigo; Rodríguez-Castellón, Enrique; Silveira Vieira, Rodrigo (RSC, 2022)
In this study, the impact of rehydration on the catalytic properties of Mg/Al layered double hydroxides (LDH) for glycerol ligomerization was assesed. Although previous works have employed other LDH derived materials in this reaction, little information on recyclability is published. After observing the initial results on how basicity and surface area were related to the catalytic activty, an LDH modification strategy was developed with the addition of acetic acid. Changes on the basic site distribution were noticed and consequently, selectivity to diglycerol was improved. The best catalytic performance (reaction with 4 wt% cat., at 240 °C for 8 hours) led to 64% of glycerol conversion (XGly) and 37% of diglycerol selectivity (Sdi). Aditionally, reciclying of modified LDH was better than the non acid treated material, presenting higher yield of diglycerol. Catalyst deactivation was related to the harsh reaction conditions and to the blockage of active species by impurities. Loss of metallic species by leaching to the reaction products was not oberseved, an advantage in comparison with previous works.
Keywords: Catálisis; Hidróxidos dobles laminares; Oligómeros (Polímeros); Acetic acid; Aluminum; Basicity; Blockage; Catalytic activity; Glycerol; Glycerols; Hydroxides; Leaching; Magnesium; Oligomerization; PH; Reaction products; Recyclability; Selectivity